The diverse and dynamic nature of Leishmania parasitophorous vacuoles studied by multidimensional imaging. - Fernando Real; Renato A Mortara (Public Library of Science (PLoS), 2012)
An important area in the cell biology of intracellular parasitism is the customization of parasitophorous vacuoles (PVs) by prokaryotic or eukaryotic intracellular microorganisms. We were curious to compare PV biogenesis in primary mouse bone marrow-derived macrophages exposed to carefully prepared amastigotes of either Leishmania major or L. amazonensis. While tight-fitting PVs are housing one or two L. major amastigotes, giant PVs are housing many L. amazonensis amastigotes. In this study, using multidimensional imaging of live cells, we compare and characterize the PV biogenesis/remodeling of macrophages i) hosting amastigotes of either L. major or L. amazonensis and ii) loaded with Lysotracker, a lysosomotropic fluorescent probe. Three dynamic features of Leishmania amastigote-hosting PVs are documented: they range from i) entry of Lysotracker transients within tight-fitting, fission-prone L. major amastigote-housing PVs; ii) the decrease in the number of macrophage acidic vesicles during the L. major PV fission or L. amazonensis PV enlargement; to iii) the L. amazonensis PV remodeling after homotypic fusion. The high content information of multidimensional images allowed the updating of our understanding of the Leishmania species-specific differences in PV biogenesis/remodeling and could be useful for the study of other intracellular microorganisms.